MENIMBANG PEMIKIRAN EKONOMI TAQYUDIN AL-NABHANI DENGAN KONSEP MAQASID AL-SHARI'AH (UINSI Samarinda, 2012)
al-Nabhani's economic thinking is built on an understanding of the texts of al-Qura'an and textual traditions and the exclusion of readings based on the maqasid shariah. Waiver maqasid shariah is evident in a variety of political opinion in which he developed the State economy. This resulted in the economic concept of the State which he developed bersifar rigid, less flexible accept new things that are useful and more serious benefits. School of thought that al-Nabhani by Yusuf al-Qaradawi called Dhahiriyah contemporary group. This is evident in the reading of al-Nabhani in the verses about the economic problems of the above, for example, thought about compulsory charity that only property is adjacent to the specified text of the Qur'an and the Hadith. Including thoughts on the idea that the authors did not describe above. Literalist readings without maqasid shariah perspective this is very dangerous and detrimental to Islam and the propagation of Islam itself. This understanding is damaging the image of Islam among contemporary scholars, among non-Muslims and even among ordinary Muslims themselves.